Technology in context: lessons from the elimination of weapons of mass destruction. Issue 1 (3rd March 2016) - Parthemore, Christine
ABSTRACT: Technology plays a central role in efforts to eliminate weapons of mass destruction (WMD). Past efforts to destroy WMD and related materials have commonly featured novel combinations of technologies designed to meet unique circumstances. In order to present the technical aspects of elimination in a context that can inform future elimination missions, this article begins by noting technology's important role. It then highlights challenges that will shape technical decisions for future missions, focusing on uncertainties, the evolution of WMD threats, the need to balance technical investments, and fighting complacency. It then offers lessons from past WMD elimination missions, including the importance of remaining innovative and agile, using a range of scenarios for planning technical options, consulting early with the full range of stakeholders who could support or challenge technical decisions, developing strong communications plans, and ensuring that plans account for critical enabling technologies. Finally, it recommends that the United States maintain elimination "on-ramps" for a range of potential future elimination missions, create a standing body to help maintain technical elimination capacity, and internationalize planning and implementation.